Evaluation of the expression of the oncogen C-ERBB-2/HER2 in advanced gastric cancer cases from Costa Rica - Cordero García, Ana Eugenia (2019)
Justification: The prevalence of gastric cancer (GC) with increased expression of the HER2 oncoprotein shows important variations worldwide. Incidence and mortality rates of GC in Costa Rica are among the highest in Latin America and the world; however, the prevalence of HER2-positive cases in this country is unknown. Evaluation of this parameter is important to decide the therapeutic approach for GC patients. The aim of this study was to provide an estimation of the prevalence of GC patients overexpressing the HER2 oncogene in Costa Rica. Methods: The investigation was carried out in two phases. The first one consisted of a retrospective review of 331 clinical records of patients diagnosed with advanced or metastatic GC from January 2010 to January 2012 in four hospitals in Costa Rica. In the second phase, immunohistochemistry (IHC) and fluorescent in situ hybridisation (FISH) analyses were performed in formalin-fixed and paraffin-embedded (FFPE) surgical samples from 50 patients diagnosed with GC between 2012 and 2015. Results: Of the 331 clinical files reviewed, the assessment of HER2 status was carried out in 62 patients (18.7%), of which only five (8%) were HER2-positive. In the 50 surgical specimens in which IHC and FISH analyses were performed, two of them (4%) presented overexpression and amplification of the HER2 oncogene. Conclusion: This study suggests that the prevalence of GC cases overexpressing the HER2 oncogene in Costa Rica is less than 8%. This is the first attempt ever undertaken to estimate the prevalence of HER2-positivity in GC in Costa Rica.